Interpretação sísmica 3D com os atributos Semelhança e Envelope do reservatório de hidratos de metano do Blake Ridge (Carolina do sul, EUA) - FARIAS, Karina Cristina Caetano (2021)
The Similarity and Envelope seismic attributes are used in this research to assess the performance in identifying and distinguishing seismic features in the Blake Ridge region of South Carolina, where there is an extensive unconventional reservoir of methane hydrates. It is used as a study method, the premise that the samples of the seismic trace are as components of a vector, and by calculating the distance in hyperspace, the Similarity attribute is defined, responsible for improving the resolution of geological faults. The Envelope attribute, is calculated as the complex function module that represents the complex seismic trace. This methodology uses the Hilbert transform, which is linearly proportional to the acoustic impedance. Through this study, it is possible to corroborate previously published geological features, discover new features and highlight the points that can support new studies.